2021
DOI: 10.1099/mgen.0.000613
|View full text |Cite
|
Sign up to set email alerts
|

Genomic insights into the diversity, virulence and resistance of Klebsiella pneumoniae extensively drug resistant clinical isolates

Abstract: Klebsiella pneumoniae has been implicated in wide-ranging nosocomial outbreaks, causing severe infections without effective treatments due to antibiotic resistance. Here, we performed genome sequencing of 70 extensively drug resistant clinical isolates, collected from Brasília’s hospitals (Brazil) between 2010 and 2014. The majority of strains (60 out of 70) belonged to a single clonal complex (CC), CC258, which has become distributed worldwide in the last two decades. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
0
6
0
1
Order By: Relevance
“…One of these was ST11, a lineage with worldwide distribution and known to cause hospital outbreaks of ESBL-and carbapenemase-producers. With such a broad distribution ST11 has a large and diverse population [5,31] yet the isolates from the same hospitals tend to be more related between them than to those of other sites [31] showing a pattern of local expansion. To understand the evolution of a large Kp-OXA hospital epidemic we have sequenced and analysed a collection of 97 ST11 Kp-OXA isolates obtained from two hospitals in Madrid during the early years of the outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…One of these was ST11, a lineage with worldwide distribution and known to cause hospital outbreaks of ESBL-and carbapenemase-producers. With such a broad distribution ST11 has a large and diverse population [5,31] yet the isolates from the same hospitals tend to be more related between them than to those of other sites [31] showing a pattern of local expansion. To understand the evolution of a large Kp-OXA hospital epidemic we have sequenced and analysed a collection of 97 ST11 Kp-OXA isolates obtained from two hospitals in Madrid during the early years of the outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…ST1264 has emerged (and probably highly restricted) in China, causing bloodstream infection, and recently associated with ESBL-producing isolates [ 56 , 57 ]. Recently, several reports indicate ST340/CC258 has a critical role in expanding NDM-producing strains in Brazil, being associated with monoclonal outbreaks, colistin-resistant-isolates, and isolates co-harboring bla NDM and bla KPC genes [ 9 , 12 , 18 , 58 ]. Epidemic ST11 was the most prevalent in our study, found dispersed in five distinct hospitals in different periods, and interestingly present in pediatric settings at H3, co-harboring bla NDM, and bla KPC , indicating endemicity and spread these resistance markers in this environment.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has demonstrated a concerning spread, with strains particularly harboring the bla NDM gene and rarely associated with bla KPC [ 54 , 61 ]. Since its first report in Brazil by Gonçalves et al [ 17 ], ST15/CC15 has been detected in clinical and environmental samples, but with few reported NDM-producing strains in Porto Alegre (South region), Rio de Janeiro (Southeast), and Brasilia (Midwest region) cities [ 9 , 50 , 54 , 62 ]. According to our data, NDM-producing ST15/CC15 strains have been found circulating in four different hospitals since 2018 and mostly present adult settings, suggesting an early and rapid spread across Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(250,252) Esse aumento de KpRC no HIAE e em outros centros de São Paulo seguem o mesmo cenário observado em outros países a partir de 2010, correlacionando o aumento da resistência à disseminação de genes de resistência adquiridos, sendo que em 2019 e 2020 os números de genes de resistência adquiridos aumentaram significativamente no mundo, semelhante ao encontrado também para ERC no HIAE em 2019 e 2020. (8) Nos períodos onde foi observado maior incidência de ERC no HIAE (207,208,253) Interessantemente, cepas ST11 também se tornaram a população predominante de Klebsiella pneumoniae em um hospital localizado na Espanha, onde foi observada a substituição de Klebsiella pneumoniae ST405 por ST11 a partir de 2014. (254) principamente um ou outro arsenal, principalmente.…”
Section: Discussionunclassified